Pengembangan Literasi Digital dalam Pembelajaran Berbicara - Haerul, Haerul; Yusrina, Yusrina (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2023)
Digital literacy is one of the skills that is really needed in the 21st century. This ability is a form of adaptation to the very rapid development of technology and information in the era of globalization. Therefore, it is best for every lesson to be integrated with the implementation of digital literacy. This research aims to describe the form of digital literacy development in speaking learning. This research is a qualitative descriptive study. The data source in this research is video documentation of digital literacy-based speaking learning. The results of this research show that the implementation of digital literacy in speaking learning can improve students' digital literacy skills.